Using smartphone video "selfies" to monitor change in toothbrushing behavior after a brief intervention: A pilot study - Parangimalai Diwakar Madan Kumar; Anusa Arunachalam Mohandoss; Theodore Walls; Thavarajah Rooban; Lance T Vernon (Wolters Kluwer Medknow Publications, 2016)
Background: Attempts to refine toothbrushing (TB) technique, an ingrained habit in adults, can meet with some challenges. Recently, the role of proactive interference as a barrier to improving the learning of proper brushing has been proposed. This pilot feasibility study was designed to investigate TB behavior and to see how it changes after training. Smartphone video "selfies" (SPVSs) are increasingly being used in the medical field to assess, monitor, and determine the progression of diseases. Materials and Methods: We used SPVS to study TB skills in a small sample of volunteers. Over a period of 14 days, after a one-time group training session, we observed TB behavior of volunteers using self-captured SPVS. Results: Following the brief intervention, we observed an 8% of improvement in TB skills. Discussion: To the best of our knowledge, this is the first report using SPVS to study TB behavior. We demonstrated initial feasibility of using SPVS in the dental setting. We observed modest improvements in toothbrushing accuracy and quality, and we generated important experiences about the use of Selfies for TB monitoring and intervention, and some interesting insights about where in the toothbrushing is more or less effective. Conclusion: Further investigation using a larger sample size is needed to thoroughly assess the effectiveness of this approach to improve TB skills and better understand the role of proactive interference.